FASTMEDICS: one stop centre / Nalini Arumugam ... [et al.] - Arumugam, Nalini; Md Razak, Mohamad Idham; Peter, Alan Basil; Sri Ramalu, Jeyarajan; Muniandy, Shanthi (2021)
The need for an integrated mobile healthcare App to bridge the government and private sector is more crucial now than before. Least we thought that our nation will have to face a pandemic such as Covid- 19. We should strive to upkeep our healthcare industry at par with the developed nations, firstly not only to curb the current pandemic more systematically but also to scale the current infrastructure system in the healthcare industry on a one-stop platform. Fastrexs (M) Sdn Bhd. is introducing FASTMEDICS – mobile healthcare App. It comes in a timely manner to render an effective and efficient tool which aims to provide solutions for the current pandemic at present. Besides, FASTMEDICS also corresponds with Ministry of Health’s (MOH) vision based on MOH report 2019.